HUBUNGAN KECERDASAN EMOSIONAL DENGAN STRES KERJA PERAWAT DI RUANG RAWAT AMBUN SURI RSUD DR. ACHMAD MOCHTAR BUKITTINGGI - Ridhyalla Afnuhazi (Universitas Baiturrahim, 2019)
The nurse has some characteristics which demand high workload and pressure. With this ability, individuals will be better able to overcome various problems that arise during the process towards adults so that they will be better able to overcome emotional challenges in modern life that are increasingly complex. Data NIOSH show 98% the nursing profession is very high risk of stres. The purpose the study was to determine the relationship between emosional intelligence and the work stres of nurses. This study use the Quasi eksperiment design with Total Sampling Method. The sample in this study were 83 respondents. This research was conducted in Inward Dr. Achmad Mochtar Hospital Bukittinggi. The statistical test used is Chi-Square. The result of statistical test showed a significant between the relationship between emosional intelligence and the work stres of nurses with p-Value = 0,000 (α ≤ 0,05). Based of the finding, it is expected that those who have nurse profession will intensively improve their emotional intelligence so that they will have lower of work stres.